The Role of Emotional Intelligence and Self-Efficacy in Career Readiness of Students with Internship Experience as a Moderating Variable - Tegowati Tegowati; Wiwin Suhada; Sari Budiarti; In’am Widiarma; Dian Palupi (Training & Research Institute - Jeramba Ilmu Sukses (TRI-JIS), 2026)
Education plays a strategic role in preparing students for the workforce, not only through academic learning but also through experiential and psychological development. Although internship experience, emotional intelligence, and self-efficacy have been widely studied as determinants of career readiness, previous findings remain inconsistent, particularly regarding the role of internship experience as a moderating variable. Some studies suggest that internships strengthen the relationship between psychological factors and career readiness, but further research is needed. A research gap was found, namely the lack of influence of self-efficacy on career readiness in students. Based on this, this study aims to examine the influence of emotional intelligence and self-efficacy on students' career readiness and analyze whether internship experience moderates this relationship. A quantitative approach was used using moderated regression analysis. The results indicate that emotional intelligence and self-efficacy have a significant positive influence on students' career readiness. Students with higher emotional intelligence demonstrate greater adaptability, decision-making skills, and readiness to face workplace challenges, while self-efficacy increases confidence in career planning and goal achievement. However, these findings also revealed that internship experience did not significantly moderate the relationship between emotional intelligence and self-efficacy on career readiness. These findings suggest that career readiness is more influenced by internal psychological factors, namely emotional intelligence and self-efficacy, than by internship experience. This study contributes to the literature by clarifying the inconsistent role of internship experience as a moderating variable and provides practical implications for universities emphasizing the development of students' emotional and psychological competencies in career preparation programs